Reoperation of Maisonneuve fracture with quadricortical syndesmotic screw, zip tight and fibula elongation by autograph: a case report in covid-19 patient - Arceri, Valerio; Di Marcantonio, Arianna; Basile, Attilio; Lanzetti, Riccardo Maria; Spoliti, Marco (Acta Biomedica Atenei Parmensis, 2022)
Purpose:. We report a Maisonneuve case of reoperation with proximal fibula fracture, diastasis of syndesmosis and parcel posterior detachment of the third malleolus. PRESENTATION OF CASES: We report a case of 49- year old patient with a Maisonneuve fracture. The first surgery has failed with three-cortical screw rupture. The second surgery was based on the implantation of quadricortical screw, zip tight and fibula elongation with autograph. The results were excellent despite the patient having contracted Covid-19 virus during rehabilitation. DISCUSSION: Maisonneuve fracture is a misdiagnosed fracture. The diagnosis may be made by RX or TC of lower limb. There are many treatments provides to stabilized and reduced the ankle. We believe the gold standard is the correct realignment of syndesmosis and a strong synthesis. CONCLUSION: The Maisonneuve fracture accounts for 7% of all ankle fractures but misdiagnosed. We emphasize the importance of making good diagnosis of this fracture for an excellent surgical result and avoiding the chronic complications of incorrect treatment. In this case the physical rehabilitation is delayed by covid-19 infection so we suggest to carry out studies on post-operative period in orthopedic patients during this global pandemic.